Smart Cities in Russia: Current Situation and Insights for Future Development - Artem Yuloskov; Mohammad Reza Bahrami; Manuel Mazzara; Iouri Kotorov (Future Internet, 2021)
The development of smart cities is a clear growing trend all around the world. The convergence of different technological, social, political, economical, and ecological trends has allowed the concepts to rise up quickly in governmental agendas. In this paper, we analyze the situation of Russia regarding smart cities. Moscow, Saint Petersburg, and Kazan are considered at the “Smart City 3.0” stage of development, meaning that the citizens are participating in their advancement. Our reasons to focus on Russia are two-fold: (1) we know the situation well, as we live and work in a new city, Innopolis, founded in 2015 and meant to be a blueprint for smart cities; (2) large Russian cities are actively developing projects in this sphere and are highly regarded worldwide in these endeavors. It is therefore worth analyzing the context and the trends. By studying the scientific literature and categorizing the features of smart cities the world over, we found that large Russian cities are developing most of the components necessary in order to be called smart. Herein we also discuss areas of possible growth for Russian cities, such as green technologies and a smart environment.